Evaluating the Protective and Detoxifying Role of Zeolite in Heavy Metal Exposure in Animal Models - Alkhatib, Ahed J (International Journal of Alternative Fuels and Energy, 2024)
Research on detoxifying living things from toxic compounds is gaining importance since many toxins have negative effects that might either directly or indirectly jeopardize human health through the environment or the food chain. The issue becomes more significant when it comes to inexpensive and plentiful elements like heavy metals and their compounds, which primarily contaminate surface, ground, subsurface, and drinking water sources. Several methods have been suggested for the cleaning of sites inaccessible to microbiological methods. Nevertheless, these methods are usually accompanied by their own side effects and inevitably contaminate the environment again or have residual toxic effects on human health during or after application. In recent years it has been observed that the minerals of the group of zeolites, which are hydrated aluminosilicates of alkali and alkaline earth metals, have the ability to detoxify soils and subsoil polluted with heavy metals. The aim of the present review is to explore the international bibliography for research on the application of zeolites in the toxicology of heavy metals. This research will hopefully contribute to a better understanding of the application of zeolites in general toxicology. Furthermore, it is suggested that the methods and the results of the studies that are described should be taken into account when experiments are carried out to investigate the effect of zeolites on the health of exposed animals.